Does home visiting improve parenting and the quality of the home environment? A systematic review and meta analysis. Issue 6 (1st June 2000) - Kendrick, Denise; Elkan, Ruth; Hewitt, Michael; Dewey, Michael; Blair, Mitch; Robinson, Jane; Williams, Debbie; Brummell, Kathy
Abstract : AIMS: To evaluate the effectiveness of home visiting programmes on parenting and quality of the home environment. DESIGN: Systematic review of the literature of randomised controlled trials and quasi-experimental studies evaluating home visiting programmes involving at least one postnatal visit. SUBJECTS: Thirty four studies reported relevant outcomes; 26 used participants considered to be at risk of adverse maternal or child health outcomes; two used preterm or low birth weight infants; and two used infants with failure to thrive. Only eight used participants not considered to be at risk of adverse child health outcomes. RESULTS: Seventeen studies reported Home Observation for Measurement of the Environment (HOME) scores, 27 reported other measures of parenting, and 10 reported both types of outcome. Twelve studies were entered into the meta analysis. This showed a significant effect of home visiting on HOME score. Similar results were found after restricting the analyses to randomised controlled trials and to higher quality studies. Twenty one of the 27 studies reporting other measures of parenting found significant treatment effects favouring the home visited group on a range of measures. CONCLUSIONS: Home visiting programmes were associated with an improvement in the quality of the home environment. Few studies used UK health visitors, so caution must be exercised in extrapolating the results to current UK health visiting practice. Further work is needed to evaluate whether UK health visitors can achieve similar results. Comparisons with similar programmes delivered by paraprofessionals or community mothers are also needed.